Tropical peat soils and transportation of greenhouse gases - Haruna, Ahmed Osumanu; Jeffary, Alicia Vanessa; Anak Luta, Wendy; Lim, Liza Nuriati Kim Choo (Universiti Putra Malaysia Press, 2018)
This book is a distillation of experiences in pineapple, tropical peats research and emission of GHGs. It is intended to provide basic information to farmers, researchers, and students about the effects of the water table fluctuation of tropical peat soils on the production and transportation of greenhouse gases during pineapple cultivation. It specifically discusses carbon dioxide, methane, and nitrous oxide production and their transportation in tropical peats cultivated with pineapples cultivation. Therefore, the book is designed as a quick reference text that enables farmers, students, and scientists to have an idea about greenhouse gas emissions from cultivated tropical peats. Chapter 1 provides general introduction on peat soils and greenhouse gases emission. Chapter 2 highlights the overview on peat soils whereas Chapter 3 details methods used in greenhouse gases measurements. Chapters 4 and 5 discuss the effects of water table fluctuation of tropical peat soils cultivated with pineapple on greenhouse gases production and transportation.